2005
DOI: 10.1021/bp050198x
|View full text |Cite
|
Sign up to set email alerts
|

Oil Wastes as Unconventional Substrates for Rhamnolipid Biosurfactant Production by Pseudomonas aeruginosa LBI

Abstract: Oil wastes were evaluated as alternative low-cost substrates for the production of rhamnolipids by Pseudomonas aeruginosa LBI strain. Wastes obtained from soybean, cottonseed, babassu, palm, and corn oil refinery were tested. The soybean soapstock waste was the best substrate, generating 11.7 g/L of rhamnolipids with a surface tension of 26.9 mN/m, a critical micelle concentration of 51.5 mg/L, and a production yield of 75%. The monorhamnolipid RhaC(10)C(10) predominates when P. aeruginosa LBI was cultivated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
2
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(114 citation statements)
references
References 23 publications
8
87
2
17
Order By: Relevance
“…The 13 C isotopologue ions with its m/z value 1 unit higher (m/z 591 and 592 for instance) showed that these species were singly charged protonated molecules, that is [M + H] + ions. To our knowledge a biosurfactant with a similar ESI(+)-MS subunit pattern for which -(CH 2 CH 2 O) n -or an isomeric unit such as -(CH 2 CH(OH)) n -seems likely and has not previously been reported (Nitschke et al 2004;Nitschke et al 2005;Jacques et al 2007;de Araújo et al 2011). FT-IR analysis of the Type I SACs from the R f 0.62 band (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The 13 C isotopologue ions with its m/z value 1 unit higher (m/z 591 and 592 for instance) showed that these species were singly charged protonated molecules, that is [M + H] + ions. To our knowledge a biosurfactant with a similar ESI(+)-MS subunit pattern for which -(CH 2 CH 2 O) n -or an isomeric unit such as -(CH 2 CH(OH)) n -seems likely and has not previously been reported (Nitschke et al 2004;Nitschke et al 2005;Jacques et al 2007;de Araújo et al 2011). FT-IR analysis of the Type I SACs from the R f 0.62 band (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Other natural compounds are biosurfactants that are surface-active compounds of microbial origin and have attracted attention due to their low toxicity and high biodegradability, when compared to synthetic surfactants (Nitschke et al 2005;Banat et al 2010). The adsorption of biosurfactants to a solid surface can modify its hydrophobicity and thus bacterial adhesion and consequently biofilm formation.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Various cheaper substrates such as soybean oil not only act as nutrients for the microbial growth but also act as an important source for isolation of potential BS producing microorganisms (Guerra- Lee et al, 2008). Rhamnolipids (RHL), one of the common BSs are usually produced on soybean oil soapstock, spent soybean oil, or chicken fat as a carbon source (Nitschke et al, , 2005. Improvement in the fermentation technology, strain selection and use of cheaper, renewable substrates have a vital role in enhancing the production processes of BS industries (Marchant and Banat, 2012b;Marchant et al, 2014).…”
Section: Introductionmentioning
confidence: 99%